Renaissance Painting and Expressions of Male Intimacy in a Seventeenth-Century Illustration from Mughal India - Natif, Mika (Renaissance and Reformation / Renaissance et Réforme, 2015)
This article explores the artistic relationship between Western European Renaissance art and Mughal painting ca. 1630s at the ateliers in North India. A central theme is the employment of European painterly modes in the Mughal visual tradition that expressed male-male intimacy, carnal desire, and emotional attachment. In particular, the article focuses on the work of the Mughal painter Govardhan, who illustrated the opening scene of Sa‘dī’s Gulistan (Rose Garden). Govardhan built upon sixteenth-century European compositional elements and the themes of Noli me tangere and the Doubting Thomas to form subtle yet unmistakable allusions to male-male sexuality.